(untitled) (Third Sector Social Economic Review, 2023)
With the rapid globalization of the world, businesses have begun to attach more importance to internationalization than ever before. Globalization, which has become quite effective as a result of advances in technology, has led businesses to develop their understanding of trade and marketing. Developments in information, communication, and transportation technologies and, changing economic and social conditions have made it easier for businesses to market their products to international markets. With the increase in globalization and digitalization, international marketing has become one of the most effective strategies for businesses to achieve their goals in international markets. In the face of the increasing importance of international marketing, the number of scientific studies is increasing at the same rate. The aim of this research is to perform a bibliometric analysis of the postgraduate theses on international marketing, which can be accessed from the website of the National Thesis Center of the Presidency of the Council of Higher Education of the Republic of Türkiye between 1982 and 2022. As a result of the research, while the majority of the postgraduate theses were composed of master’s theses, it was determined that the language of writing was mostly Turkish. It is seen that the prepared postgraduate theses are mostly published in the universities, social sciences institutes, and management departments in Istanbul and Izmir. In addition, it has been determined that the theses are mostly studied in business, and international marketing is used as a keyword.